(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Pronunciation is a crucial aspect of mastering English, as it directly affects communication clarity and comprehension. Many English learners struggle with pronunciation due to differences in phonetics, stress patterns, and intonation compared to their native language. Improving pronunciation requires consistent practice, the right techniques, and effective resources. This article gives some helpful tips to improve pronunciation of 8th grade people.